Intensive Follow-Up After Curative Surgery for Colorectal Cancer - Rodrigues, Rita Vale (2017)
Introduction: The purpose of postoperative surveillance programs after curative treatment for colorectal cancer is to detect asymptomatic recurrences with the premise that an important rate will be eligible for curative resection, improving overall survival. We have implemented a surveillance program for patients with colorectal cancer, stages II-III, with periodic clinical, carcinoembryonic antigen and cancer antigen-19-9 assessment, computed tomography and colonoscopy. The aim of this study was to assess the rate of curative treatment of recurrence, colorectal cancer mortality and clinical characteristics associated with non-resectable recurrence.Material and Methods: Open cohort study, single center. All patients on the intensive surveillance program between March 2008 and January 2015 were included. Statistics: chi-square, Wilcoxon rank sum test, logistic regression, Kaplan-Meier log-rank test (SPSS20®).Results: We had a total 404 patients evaluated; 59.6% male; mean age of 65 ± 10 years; 50.7% rectal tumor; 56.2% stage III. The average time of follow-up was 37 months and the recurrence rate was 12.9% (n = 52), mostly detected in the first three years (88.4%). The pattern of recurrence was associated with the site of the primary tumor (p < 0.001). Twenty-one patients underwent curative resection. Factors associated with non-resectable recurrence were aged ≥ 70 years (p = 0.022), disease location in the colon (p = 0.033) and cancer antigen-19-9-9 elevation (p = 0.024). The overall rate of cancer-specific mortality was 2.2% (n = 9).Discussion: The association between colon cancer and non-resectable recurrence is explained by the higher rate of disseminated disease in these patients. Cancer antigen-19-9 added no benefit to the surveillance program.Conclusion: This intensive real-world postoperative surveillance program allowed performing curative surgery to 40.3% of patients with recurrence.